Wallace Stevens. - Tindall, William York, 1903-1981 (University of Minnesota pamphlets on American writers ;, 1961)
Wallace Stevens - American Writers 11 was first published in 1961. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.